An integrated decision-making framework for existing building retrofits based on energy simulation and cost-benefit analysis. (November 2021) - Lu, Yujie; Li, Peixian; Lee, Yih Perng; Song, Xiangnan
Abstract: Future city renewal and rejuvenation require a tremendous amount of existing building retrofits to improve energy efficiency for sustainable city development. Although energy retrofit has received much attention, there lacks a comprehensive workflow for institutional buildings in a tropical climate. This paper proposes an easy-to-follow framework for optimal decision-making of energy retrofit with a detailed case study on a multi-purpose building on the National University of Singapore campus. The framework integrates energy simulation, a hybrid approach to quantify retrofit benefits, cost contextualization procedure, standardized cost-benefit analysis plots and indicators, and a final decision matrix. Among the analyzed retrofit options, occupants-oriented retrofit options such as installing occupancy sensor for automatic lighting control, setting higher temperature setpoint, and lowering plug load, topped the selection with scores 8.63, 7.18, and 7.09 respectively, significantly outperforming the technological retrofit like replacing water-cooled chiller (score 3.19) and installing a green roof (score 1.42). Furthermore, taking multiple occupants-oriented retrofits together involves less cost per energy saving than taking each of them individually. This indicates that combined measures could augment the cost-effectiveness of building energy retrofit. This work offers a hands-on framework for decision-making on energy retrofits and implications for developing more comprehensive guidelines for city renewal. Highlights: We proposed an integrated framework for energy retrofit of existing buildings. The framework mainly consists of energy simulation and cost-benefit analysis. The case study showcases recommended plots and decision-making KPIs. Occupants-oriented retrofits outperformed heavily technological retrofits. Combined measures are more cost-effective than single measures.